Digital Leadership and Innovation: A Systematic Literature Review of Theoretical Foundations, Research Emphases, and Methodological Approaches - Gunawan; Budi Santoso; Muhammad Ifan Fadillah; Dadar Supriatna (CAKRAWALA : Management Science Journal, 2025)
Digital leadership is increasingly recognized as a strategic capability essential for guiding organizations through rapid technological transformation. It is particularly associated with enhanced agility, performance, and the integration of emerging technologies across sectors such as SMEs, manufacturing, education, and public administration. Despite growing interest, existing literature remains fragmented and lacks a coherent synthesis that reflects the multidimensional role of digital leadership across varying organizational and contextual settings. Moreover, limited attention has been given to the mechanisms through which digital leadership drives innovation under diverse ecological, geographic, and structural conditions. To address this gap, we conduct a Systematic Literature Review (SLR) following PRISMA 2020 guidelines and the SPAR-4-SLR framework, analyzing 43 peer-reviewed Scopus-indexed articles published between 2015 and 2025. Through thematic synthesis, bibliometric mapping, and theoretical classification, we identify key patterns, conceptual structures, and research trends. The findings highlight the dominance of Dynamic Capability Theory (DCT) and Resource-Based View (RBV), with survey-based SEM methodologies prevailing. Notable gaps include conceptual ambiguity, methodological uniformity, and limited longitudinal and cross-cultural insights. This review offers a future research agenda grounded in the Theory–Context–Method (TCM) framework, advocating for broader theoretical integration and contextual diversity to better understand digital leadership’s role in fostering sustainable innovation.